2017
DOI: 10.1194/jlr.m071258
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of homologous sphingosine-1-phosphate lyase isoforms in the bacterial pathogen Burkholderia pseudomallei

Abstract: Sphingolipids (SLs) are ubiquitous elements in eukaryotic membranes and are also found in some bacterial and viral species. As well as playing an integral structural role, SLs also act as potent signaling molecules involved in numerous cellular pathways and have been linked to many human diseases. A central SL signaling molecule is sphingosine-1-phosphate (S1P), whose breakdown is catalyzed by S1P lyase (S1PL), a pyridoxal 5′-phosphate (PLP)-dependent enzyme that catalyzes the cleavage of S1P to (2E)-hexadecen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…These organisms do not encode SL biosynthesis genes but genome analysis revealed that Burkholderia pseudomallei K96243, a category B biothreat agent, encodes two homologous proteins (S1PL2021 and S1PL2025) that display moderate sequence identity to known eukaryotic and prokaryotic S1PLs. 277 , 278 Both homologs were isolated and shown to catalyse S1PL-dependent conversion of S1P to 2 E -HEX and PEA using a convenient fatty aldehyde dehydrogenase (FALDH) dependent coupled assay. The crystal structure of the B. pseudomallei S1PL2021 ( Fig.…”
Section: Sphingosine 1-phosphate Lyase (S1pl)mentioning
confidence: 99%
“…These organisms do not encode SL biosynthesis genes but genome analysis revealed that Burkholderia pseudomallei K96243, a category B biothreat agent, encodes two homologous proteins (S1PL2021 and S1PL2025) that display moderate sequence identity to known eukaryotic and prokaryotic S1PLs. 277 , 278 Both homologs were isolated and shown to catalyse S1PL-dependent conversion of S1P to 2 E -HEX and PEA using a convenient fatty aldehyde dehydrogenase (FALDH) dependent coupled assay. The crystal structure of the B. pseudomallei S1PL2021 ( Fig.…”
Section: Sphingosine 1-phosphate Lyase (S1pl)mentioning
confidence: 99%
“…S1P is thought to be involved in the progression from IBD to cancer [53]. It may be that two homologous proteins (S1PL2021 and S1PL2025), which were recently reported in the pathogenic bacterium Burkholderia pseudomallei K96243, degrade host sphingolipids (SLs) via a mechanism mediated by the pyridoxal 5 0 -phosphate (PLP)dependent enzyme S1P lyase (S1PL) [54]. Exosomes secreted by enterobacteria trigger the intestinal epithelium to produce exosome-like nanoparticles derived from mucosa, which contain S1P, chemokine (C-C motif) ligand 20 (CCL20, macrophage inflammatory protein-3, MIP3A), and prostaglandin E2 (PGE2), which, in turn, promote Th17 cells and modulate intestinal inflammation [55].…”
Section: Pathogenic Stimulusmentioning
confidence: 99%
“…SPL-deficient mutants of Burkholderia sp. displayed impaired intracellular replication in murine macrophages [ 84 , 85 ]. The findings suggest that the bacterium secretes SPL to remove host-generated intracellular S1P, which somehow facilitates its survival and replication.…”
Section: Structure and Functions Of Splmentioning
confidence: 99%